Helical bottleneck effect in 3D homogeneous isotropic turbulence. (3rd January 2018) - Stepanov, Rodion; Golbraikh, Ephim; Frick, Peter; Shestakov, Alexander
Abstract: We present the results of modelling the development of homogeneous and isotropic turbulence with a large-scale source of energy and a source of helicity distributed over scales. We use the shell model for numerical simulation of the turbulence at high Reynolds number. The results show that the helicity injection leads to a significant change in the behavior of the energy and helicity spectra in scales larger and smaller than the energy injection scale. We suggest the phenomenology for direct turbulent cascades with the helicity effect, which reduces the efficiency of the spectral energy transfer. Therefore the energy is accumulated and redistributed so that non-linear interactions will be sufficient to provide a constant energy flux. It can be interpreted as the 'helical bottleneck effect' which, depending on the parameters of the injection helicity, reminds one of the well-known bottleneck effect at the end of inertial range. Simulations which included the infrared part of the spectrum show that the inverse cascade hardly develops under distributed helicity forcing.